A 6-year review of maternal outcomes for second stage cesarean section in Hospital Universiti Sains Malaysia - Rashid, Nurul Nafizah Mohd (2018)
Objectives: To determine the prevalence of cesarean section performed in the second stage of labour and to identify the maternal outcomes and its associated risk factors in these women. Study design: This retrospective study was carried out in the Hospital University Sains Malaysia (HUSM). Medical records of 207 women with singleton cephalic pregnancies at term, identified from the hospital database, who underwent a second stage cesarean section (SSCS) between 1st January 2010 and 31st December 2015, were reviewed and demographic and outcome data were collected. Results: During the study period 8197/42,546 (19.3%) babies were delivered by CS. Two hundred and fifty seven CS (4.1%) were performed in the second stage of labour. Almost half of the women were nulliparous (49.3%) and 87.9% had spontaneous labour and 59.4% (n=123) had oxytocin augmentation. There were 48 (23.2%) whom had previous cesarean sections and 147 (71.1%) had the station below zero (62.3%, 7.7% and 1.0% for station 0, +1 & +2 respectively). 85.5% of women had a second stage CS without a trial of instrumental delivery. The mean duration of second stage in this study was 144 (±56.2) minutes and mean estimated blood loss was 545 (±357) mls. 12.6% of women (n=26) had postpartum hemorrhage (greater than or equal to 1000mls). 10.6% (n=22) of these women required blood transfusion. Only 1 woman (0.5%) need to be admitted to intensive care unit post-operatively. 78.7% (n=163) had the overall length of hospital stay for 3 days. 18.4% (38) and 15.9% (33) of women had extended uterine tear and uterine atony respectively. Otherwise none of the women sustained neither cervical tear nor bladder injury. The parity (p<0.001), attempted instrumentation (p<0.001), and baby weight (p<0.004) were statistically significant association with the total blood loss. The risk factors for extended uterine tear was statistically significant associated with parity (p<0.012) and attempted instrumentation (p<0.001) respectively. Conclusions: The overall outcomes of second stage CS performed in HUSM is comparable to studies done in other centres. Current practices need to be maintained or improved especially with regards to meticulous documentation and training of junior obstetric staff to provide the best care for the patients.